Nanobubble assisted flotation separation of complex Pb–Cu–Zn sulfide ore – Assessment of process readiness. Issue 8 (24th May 2022) - Chipakwe, Vitalis; Sand, Anders; Chelgani, Saeed Chehreh
ABSTRACT: A considerable difference exists between the flotation separation of artificial minerals and real low-grade ores processing where selectivity would be the main issue. Nanobubble-assisted (NB) flotation investigations have been mostly examined with pure materials and a narrow particle size range, less on complex sulfide ores. This study considered NB flotation for processing complex Pb-Cu-Zn sulfide ore in two different size ranges and various conditions to assess the process readiness. Metallurgical NB flotation responses (recovery, grade, kinetics, and selectivity index) were determined, compared to conventional tests. Outcomes revealed that an inclusive size fraction (−150 µm) could result in a higher selective process than a fine fraction (- 38 µm). In contrast, mass recovery and kinetics were higher for the fine one. In general, adding NBs compared to the conventional (CB) could improve the flotation metallurgical responses; however, the way NBs were generated would be key. NBs generated in the presence of frother (NBF) could produce higher mass and water recoveries while decreasing selectivity. In general, different setups' flotation products showed the following selectivity order of Pb-Cu sulfides: NB>NBF>CB. These results opened a new approach for considering different NB generation conditions when they are going to use in various flotation stages.